Моделювання руху двомасового вібраційного живильника на базі гідроімпульсного привода - Іскович - Лотоцький, Р. Д.; Коц, І. В.; Іванчук, Я. В.; Івашко, Є. І.; Искович - Лотоцкий, Р. Д.; Коц, И. В.; Иванчук, Я. В.; Ивашко, Е. И.; Iskovych-Lototskyi, R.; Kots, I.; Ivanchuk, Y.; Ivashko, Y. (ЦНТУ, 2018)
Розроблена нова оригінальна конструкція двомасового вібраційного живильника на базі гідроімпульсного привода, яка врівноважує надлишкові динамічні навантаження. Проведено теоретичне дослідження двомасового вібраційного живильника з гідроімпульсним приводом на базі розробленої математичної моделі. У процесі дослідження була розроблена розрахункова схема пристрою та отримані основі математичні залежності які характеризують режими його роботи та взаємозв’язок робочих параметрів, а також дають змогу оцінити актуальність та перспективність оригінальної розробки. Разработана новая оригинальная конструкция двухмассового вибрационного питателя на базе гидроимпульсного привода, которая уравновешивает избыточные динамические нагрузки. Проведено теоретическое исследование двухмассового вибрационного питателя с гидроимпульсным приводом на базе разработанной математической модели. В процессе исследования была разработана расчетная схема устройства и получены основные математические зависимости, что характеризуют режимы его работы и взаимосвязь рабочих параметров, а также дают возможность оценить актуальность и перспективность оригинальной разработки. The main disadvantage of powerful vibrating feeders with different types of drives, performed on a single-mass scheme, are high dynamic loads on the elements of load-bearing structures. The aim of the article is to develop a mathematical model of the motion of a two-mass vibrating feeder based on a hydroimpulse drive, to confirm the feasibility of developing and its performance in the future. Vibrating feeders with a hydropulse drive are tuned to near resonance mode, as a result of which the dynamic load on the foundation can reach very high values. The solution to this problem is to establish an additional reactive mass, which will absorb the excessive dynamic loads. A new original design of a two-mass vibrating feeder based on a hydropulse drive is developed, which balances the excess dynamic loads. A mathematical model of the motion of a two-mass vibrating feeder is developed, which is represented by a system of Lagrange differential equations. The solution of the mathematical model of motion of a vibrating feeder was carried out by the method of introducing a complex variable. A theoretical investigation of a two-mass vibrating feeder with a hydroimpulse drive based on the developed mathematical model is carried out. In the process of research, the design scheme of the device was developed and the mathematical dependences obtained on the basis of a system of differential equations were derived. A mathematical model of the motion of a vibrating feeder has been developed which allows to optimize the parameters of debugging of the hydroimpulse drive and to outline ways to solve the problem of extremely high dynamic loads on the foundation while developing new original designs of two-mass vibrating feeders. Solving the system of differential equations that characterize the modes of its operation and the interrelationship of operating parameters make it possible to assess the relevance and prospects of the original development.
Моделирование движения двухмассового вибрационного питателя на базе гидроимпульсного привода
Simulation of the Motion of a Two-mass Vibrating Feeder Based on a Hydro-impulse Drive
Keywords: вібрації; реактивна маса; вібраційний живильник; гідроімпульсний привод; гидроимпульсный привод; вибрации, реактивная маса; вибрационный питатель; reactive mass; two-mass vibration feeder; hydro-impulse drive; vibration